Legal republicanism national and international perspectives - Besson, Samantha, 1973-; d (Oxford : Oxford University Press, 2009)
Interest in republicanism as a political theory has burgeoned in recent years, but its implications for the understanding of law have remained largely unexplored. This book offers a comprehensive, critical survey of the potential for creating republican accounts of fundamental issues in law and legal theory.
"Outcome of the workshop on Law and Republicanism - National and Post-National Perspectives that took place from 2 to 4 August 2007 in Krakow (Poland) in the framework of the XXIIIrd IVR World Congress of Philosophy of Law and Social Philosophy." --Pref.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International law -- Philosophy -- Congresses; Law -- Political aspects -- Congresses; Republicanism -- Congresses